Pengaruh Periodisasi Terhadap Kualitas Pelayanan Kenaikan Pangkat Pegawai Negeri Sipil - Klara Bali; Lingga Yuliana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to determine the effect of adding a civil servant promotion period on the quality of civil servant promotion services within the Sekadau Regency Government. The method used in this study is a qualitative approach method. The sample collection technique uses purposive sampling where respondents are determined with the criteria of being ASN who work at the Sekadau Regency Human Resources Development and Personnel Agency. Based on the results of the study, it was found that periodization has an effect on the quality of service. Overall, the change in the promotion period from twice a year to six times a year has a positive impact in terms of efficiency and career opportunities for civil servants.